Bibliography: Migration, Urbanization And Marginality In Peru - Abugattas, Luis (Universidad del Pacífico, 1979)
Bibliography about migration, urbanization and marginality in Peru, collected in the National Library, the Universidad del Pacífico and ESAN (Pontificia Universidad Católica del Perú).